Working Experience at IT and HR Department in BRITISH AERICAN TOBACCO BANGLADESH - Jannat, Meftahul (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.